Вихідний потік зв'язуючого нейрона - Відибіда, О.К. (Український математичний журнал, 2007)
Для связывающего нейрона с порогом 2, стимулированного пуассоновским потоком, вычислена интенсивность выходного потока и плотность распределения вероятности длин выходных межимпульсных интервалов. Для порога 3 вычислена интенсивность выходного потока. For a binding neuron with threshold 2 stimulated by a Poisson stream, we determine the intensity of the output stream and the probability density for the lengths of the output interpulse intervals. For threshold 3, we determine the intensity of the output stream.